Power system state and transmission line conductor temperature estimation - Chawasak Rakpenthai (2018)
© 1969-2012 IEEE. This paper presents a state estimation technique for three-phase power systems where not only bus voltage phasors but also the temperature of transmission line conductors is considered as states. Transmission line admittance parameters depending on line conductor and ambient temperature are approximated from the pre-computed data based on polynomial interpolations. Weather environment and heat-balance equations have been also included in the measurement functions in order to estimate the temperature of conductors. The technique for segmenting transmission lines is also applied for handling temperature variations along the lines. The estimation problem is then formulated as a constrained nonlinear optimization based on the weighted least-squares criterion. A solution is obtained by applying a predictor-corrector interior point algorithm. Simulation results on some three-phase power systems indicate that the proposed method yields estimations with a better accuracy.